Implementação de políticas públicas e relações intergovernamentais: uma análise da legislação sob a perspectiva dos dilemas de ação coletiva no transporte público coletivo da Região Metropolitana de Curitiba (RMC) - Cavalcante, João Paulo de Souza (2015)
Metropolitan areas present clearly the greatest dichotomies in Brazilian society. Wealth and poverty, quality of life and lack of opportunities. In this sense, some of the bad results in terms of public policies can be associated with problems in its implementation. In this study, the analysis relies in the intergovernmental relations between the municipalities that composes the Metropolitan Region of Curitiba (RMC) and the state of Paraná, all of them responsible for the implementation of public transportation policies. The difficulty in dealing with the dilemmas of collective action, intrinsic to the implementation of policies, federalism, the conformation of metropolitan region itself and even the provision of public transportation systems is the assumption underlying this research. To carry out the analysis, it was used a qualitative approach, with exploratory and descriptive objectives. This research used bibliographic and documentary approach to accomplish its objectives. Regarding to the later approach, the procedure was to analyze the collected documents that included the whole legislation that regulates the implementation of public transport policies in the metropolitan region of Curitiba. The document analysis sought to identify the presence or absence of certain concepts related to coordination and cooperation for the implementation of public policies in interactive contexts. The results led to the following conclusions: a) although the legislators recognize the necessity for cooperation in public policy there are no pattern to follow; b) there have been three distinct phases for cooperation, starting with the imposition of norms by the Union, going through a phase of extreme decentralization and the current one, where seem to appear the first patterns for collective action; c) current pattern seems to be the establishment of public consortia and interfederative governance in metropolitan areas. Conclusions lead to the understanding that the rules governing the implementation of public transport policies in the RMC are at the same time, problems and obstacles to the expected cooperative behavior, because on the one hand, they stimulate competition between the entities and the hierarchical superiority of some over others. On the other hand it recognizes the need for collective action. Even so, for more than 20 years the RMC managed to maintain an integrated network of active transport, which suggests the active participation of the individuals responsible for this policy.